Pengaruh Stres, Motivasi dan Kepuasan Kerja Terhadap Kinerja Pegawai : Studi Pada Pegawai Non Medis di RS Bhayangkara Manado - Tumbuan, Uguy, Tumbel, (Universitas Sam Ratulangi, 2018)
The high performance of employees will have a good impact on the progress of the hospital in the future. This research would be able to provide solutions and advice for hospitals to raise morale by increasing the effectiveness of work and a good working relationship from the perspective of stress, motivation and job satisfaction of non-medical employees in RS Bhayangkara Manado. Results from this study is the negative effect of stress, but no significant effect on performance, motivation significant positive effect on employee performance and job satisfaction significantly negative effect on the performance of non-medical employees in RS Bhayangkara ManadoKeywords: Stress, Motivation, Job Satisfaction and Employee Performance